Productivity in mechanizing early tending in spruce seedling stands - Routa, Johanna (Array, 2019)
According to National Forest Inventory data, there is an urgent need for tending seedling stands of at least 700,000 ha and a need for 1 million ha in the next few years in Finland. The motivation for forest owners to conduct pre-commercial silvicultural operations is low due to the associated high costs. Especially the costs of tending and clearing operations after the regeneration of the stand have been increasing. In addition, the availability of labor is a restricting factor due to the high seasonality of silvicultural works. In the 2000s, several solutions for the mechanization of tending have been proposed. These are based on the use of harvester or a forwarder as a base machine. Typically, light weight base machines are favored to reduce the hourly cost of operations and the impacts on the remaining seedlings. There have been challenges with the high speed of the cutting device, which increases the risk of damages to the head and the ignition of forest fires when the circular saw or chain hits stones, for example. In addition, the chain can become dislocated due to bending forces caused by stumps. Cutlink has presented a low RPM solution based on rotating cone-shaped shears that cut 50–100 cm wide corridors between and around seedlings. In this study, the productivity of mechanized tending with Cutlink´s device compared to manual tending was evaluated in spruce seedling stands in central Finland. The productivity, fuel consumption and quality of the seedling stand after the operation were measured. In early tending, the productivity of motor manual tending was notably better than when using the Cutlink device. Crucial factors for the competitiveness of a mechanized alternative include the annual working hours and finding suitable working areas for the machine. Additional work for the device and base machine can also be found in the clearing of forest road sides.